DEVELOPMENT OF NEW HIGHLY ACTIVE L-ALANINE PRODUCER STRAINS OF BREVIBACTERIUM FLAVUM AND COMPARATIVE CHARACTERIZATION OF THEIR ALANINE-SYNTHESIZING ACTIVITY - G. Ye. Avetisova; L. H. Melkonyan; A. Kh. Chakhalyan; S. Gh. Keleshyan; A. S. Saghyan (Вавиловский журнал генетики и селекции, 2015)
New mutants, not described previously, resistant to L-cycloserine and β-chloro-L-alanine were derived from the parental strain Brevibacterium flavum AA5. Their alanine-producing ability was studied. It was found that the resistance to L-cycloserine did not affect the yield of L-alanine significantly, whereas the resistance to β-chloro-L-alanine of B. flavum GL1 and B. flavum GL18 strain-producers exceeds the initial level of L-alanine synthesis by 23 and 38 %, respectively.